Analisis pengaruh nilai ekspor, impor, dan inflasi terhadap kurs rupiah - Utami, Novia Tri (ARKA INSTITUTE, 2023)
Indonesia as a country rich in natural resources has better international trade performance in increasing the exchange rate. This study aims to determine the effect of exports, imports and inflation on the rupiah exchange rate per US dollar during 1987-2019. The data used are secondary data sourced from the World Bank, the method used is a quantitative approach by applying a time series data model. This is an error correction model or ECM (Error Correction Model). The results of this study indicate that exports and imports have a significant negative effect on the exchange rate in the short term and a positive effect in the long term, while inflation has a positive effect on the exchange rate in the long term and a negative effect in the short term. So it can be concluded that exports and imports only have a short-term effect on the exchange rate while inflation has a long-term effect on the rupiah exchange rate.